Demystifying opportunistic infections in an AIDS patient of 21st century in Nepal - Bhattarai, Sanjeet; Shah, Devendra; Rayamajhi, Sulav; Bhusal, Yuvaraj; Khanal, Kishor; Upadhyaya, Prabhaw; Shrestha, Sanjeet Krishna (Journal of Advances in Internal Medicine, 2021)
Currently, there is no cure for Human immunodeficiency virus /Acquired immunodeficiency syndrome (HIV/AIDS) but, there are medications to control HIV and prevent opportunistic infections. Clinicians must be vigilant enough to extract history and send relevant laboratory investigations to diagnose the disease in early stage. Patient may not have known his /her diagnosis or intentionally avoided to reveal the disease status which further complicates the diagnosis and treatment. This is case of a 51 years male, where social stigma forces the patient to hide his diagnosis and reluctant to seek medical treatment ultimately reaps the life. Hence, government and concerned authority must work up for wide availability of HIV/AIDS medications and motivate people to seek medical advices as soon as possible. Concerned authority must motivate people to consider it as any other treatable disease.